PERAN SERIKAT PEKERJA DALAM MENGHADAPI REVOLUSI INDUSTRI 4.0 PADA SEKTOR INDUSTRI OTOMOTIF - Haspul Naser; Budi Safari; Kunto Atmojo (Unitri Press, 2020)
The purpose of this study was to determine the partnership model between Trade Unions and Management in the face of the Industrial Revolution 4.0. The total sample used was 100 employees in the field of vehicle assembly. The processed data produced there is a